2012
DOI: 10.4141/cjas2011-040
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of commonly used and novel electronic techniques for evaluating cattle temperament

Abstract: Schwartzkopf-Genswein, K. S., Shah, M. A., Church, J. S., Haley, D. B., Janzen, K., Truong, G., Atkins, R. P. and Crowe, T. J. 2012. A comparison of commonly used and novel electronic techniques for evaluating cattle temperament. Can. J. Anim. Sci. 92: 21–31. The temperament of steers (n=28) was assessed using five quantitative techniques including: flight time, flight distance, electronic (strain-gauge and accelerometer) tests, and three visual scores (VS) made during entry, restraint and exit from a squeeze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…These applications indicate that traditional subjective scoring techniques can be replaced with more repeatable objective measures for example, when temperaments are assessed for performance studies (Maffei et al, 2006;Maffei, 2009;Sebastian et al, 2011;Schwartzkopf-Genswein et al, 2012).…”
Section: Objectivity Of Methods For the Assessment Of Cattle Behaviourmentioning
confidence: 98%
“…These applications indicate that traditional subjective scoring techniques can be replaced with more repeatable objective measures for example, when temperaments are assessed for performance studies (Maffei et al, 2006;Maffei, 2009;Sebastian et al, 2011;Schwartzkopf-Genswein et al, 2012).…”
Section: Objectivity Of Methods For the Assessment Of Cattle Behaviourmentioning
confidence: 98%
“…Heritabilities and additive genetic variance show that besides environmental components such as food, fetching and machine calibration (e.g., restriction of the INT) there is a genetic component behind the traits. Research showed that there is a possibility to automatically record behavior traits (König et al, 2006;Schwartzkopf-Genswein et al, 2012). The characterization of the traits in the context of animal welfare implies further studies including temperament and behavior tests as validated in animal ethology (e.g., Ebinghaus et al, 2017).…”
Section: Variance Components and Heritabilities For Behavior Traitsmentioning
confidence: 99%
“…A field study was designed to attempt to validate the marketing claims made by the proponents of the product by measuring the impacts of feeding winery by-products on beef cattle flight speed (FS), a quantitative behavioural assessment tool which has been widely used as a measure of beef cattle temperament and has been correlated with weight gain in cattle (Muller & von Keyserlingk, 2006;Petherick et al, 2009;Schwartzkopf-Genswein et al, 2012;Stockman et al, 2012). After animal weights were recorded and cattle ID was determined via Radio-Frequency identification tags (RFID) tags, the flight speed of cattle was evaluated.…”
Section: Flight Speedmentioning
confidence: 99%
“…Temperament in cattle has been defined and measured in numerous ways, the most common of which involves an animal's response to handling (Schwartzkopf-Genswein et al, 2012). Past research has indicated that animals that differed in their FS also exhibited differences in their personality traits, which has often resulted in differences in their average daily gain (Muller and von Keyserlingk 2006).…”
Section: Introductionmentioning
confidence: 99%